2001
DOI: 10.1002/1096-8628(20010615)101:2<120::aid-ajmg1319>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of linkage to the CDL1 gene region on chromosome 3q26.3 in some familial cases of Cornelia de Lange syndrome

Abstract: Cornelia de Lange Syndrome (CdLS) is a complex developmental disorder consisting of characteristic facial features, limb abnormalities, hirsutism, ophthalmologic involvement, gastroesophageal dysfunction, hearing loss, as well as growth and neurodevelopmental retardation. Most cases of CdLS appear to be sporadic. Familial cases are rare and indicate autosomal dominant inheritance. Several individuals with CdLS have been reported with chromosomal abnormalities, suggesting candidate genomic regions within which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In a few cases familial transmission has been inferred by the recurrence of affected sibs, from an apparently normal couple, both carrying the same mutation in NIPBL (4,11). Moreover, the report of an unaffected father with two daughters with CdLS, from two non-related spouses, suggested that gonadal mosaicism plays a role in the recurrence of CdLS (13). The germline mosaicism theory has been nicely demonstrated by Niu et al who found the same NIPBL mutation in the DNA of sperms from the father of two siblings (14).…”
Section: Discussionmentioning
confidence: 99%
“…In a few cases familial transmission has been inferred by the recurrence of affected sibs, from an apparently normal couple, both carrying the same mutation in NIPBL (4,11). Moreover, the report of an unaffected father with two daughters with CdLS, from two non-related spouses, suggested that gonadal mosaicism plays a role in the recurrence of CdLS (13). The germline mosaicism theory has been nicely demonstrated by Niu et al who found the same NIPBL mutation in the DNA of sperms from the father of two siblings (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the complex t(3;12), one of the breakpoints maps at 3q26.3, previously suggested as a candidate region for Cornelia de Lange syndrome, CdLS (Ireland et al 1991;Krantz et al 2001;Faas et al 2002). However, the causative gene for CdLS has been subsequently shown to be NIPBL initially identified by breakpoint mapping in a CdLS patient with a t(5;13)(p13.1;q12.2) (Borck et al 2004;Krantz et al 2004;Tonkin et al 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…After collaborative linkage analyses excluded the 3q26-27 region in some rare multicase families [8], we prioritised the study of breakpoints in t(14;21)(q32;q11) and t(5;13)(p13.1;q11.2) translocation cases [9 ]. Following a report of a del(5)(p13.1p14.2) CdLS case, the 5p13 breakpoint was extensively characterised and found to sever intron 1 of a previously uncharacterised gene in which nine additional CdLS-specific mutations were found (five of them shown to arise de novo) [9 ].…”
Section: Approaches To Gene Identificationmentioning
confidence: 99%